2020
DOI: 10.1080/09687599.2020.1749563
|View full text |Cite
|
Sign up to set email alerts
|

Is digital inclusion fighting disability stigma? Opportunities, barriers, and recommendations

Abstract: This paper presents a focus group study of the role of digital inclusion in overcoming disability stigma. It reviews stigma literature and contrasting disability models, ultimately arguing the value of the biopsychosocial approach to the role of digital inclusion in disability stigma. The paper qualitatively explores the stigma experienced by people with disabilities and the ways in which digital inclusion might affect such experiences. It asserts that the benefits of digital inclusion depend, simultaneously, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 59 publications
0
30
0
11
Order By: Relevance
“…The focus group is a qualitative explanatory tool that explores perceptions and attitudes of a small group of people that interact and discuss a topic allowing their considerations [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. A high number of interactions taking place in the focus group [ 54 ] foster a participative climate encouraging people to discuss and reflect upon a given topic in depth [ 55 ]. It is important to consider the context of the focus group setting as it is a determinant factor for the discursive production and its socio-cultural meaning [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…The focus group is a qualitative explanatory tool that explores perceptions and attitudes of a small group of people that interact and discuss a topic allowing their considerations [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. A high number of interactions taking place in the focus group [ 54 ] foster a participative climate encouraging people to discuss and reflect upon a given topic in depth [ 55 ]. It is important to consider the context of the focus group setting as it is a determinant factor for the discursive production and its socio-cultural meaning [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…The internet allows PWD to form and maintain relationships and community in ways that may not be possible offline. Going online, PWD have more control over whether and how to disclose disabilities that might be readily apparent in face-to-face interaction, thus managing stigma ( Saltes, 2013 ; Soderstrom, 2009 ; Tsatsou, 2020 ). At other times, PWD can put their impairments or health conditions in the forefront of interactions online, using ICTs to join communities of others who share their condition ( Goggin & Noonan, 2006 ).…”
Section: Disability Isolation and The Internetmentioning
confidence: 99%
“…The Convention on the Rights of Persons with Disabilities (United Nations, 2006) was a milestone in the struggle against the exclusion suffered by people with disabilities within the UN human rights system, even though its recognition in subsequent agreements has only sometimes been comprehensive, often limited to formal statements (Skarstad and Stein, 2018). Today, there continues to be a clash between personal identity and the social construction of disability (Tsatsou, 2020). Stigma, discrimination, and social exclusion of this group has been continual from the point of view of societal aspects, health, transport, housing, education, employment, and public services, as well as the negative image transmitted through the media (Oliver, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Social networks also allow individuals to control how and when they disclose information about their disability based on their online relationships, or in other words, whether they choose to do so in a way that is open, safe, or limited (Furr, Carreiro and McArthur, 2015). However, it seems that the psychological benefits of using digital technology result primarily from the anonymity with which people with disabilities interact on the Internet and social networks (Tsatsou, 2020), although a person can build their identity in a positive way until they decide to disclose their disability (Bowker and Tuffin, 2002). The most recent studies conducted in medical centres have revealed that half of the patients surveyed who have intellectual and/or developmental disabilities do not use mobile devices (44.6%), and that the majority (86.8%) do not use social networks (Patrick et al, 2020).…”
Section: Introductionmentioning
confidence: 99%